THE IMPORTANCE OF INTERACTIVE METHODS IN THE EDUCATIONAL PROCESS - Juraeva Barchinoy Meylievna (Galaxy International Interdisciplinary Research Journal, 2022)
Today, students' education and the success of the educational process are dependent on the use of pedagogical technologies in industrialized countries, which encourages creative activity. Numerous experiences have been gained, and interactive approaches are organized based on these experiences.